First record of Heteropsylla tenuata from Argentina (Hemiptera: Psyllidae), and additional notes on other psyllid species - Baliotte, Carla; Aquino, Daniel Alejandro; Bouvet, Juan Pedro; Dellapé, Gimena (Sociedad Entomológica Argentina, 2022)
The Psyllidae family is the most diverse within Psylloidea, with more than 1,300 species worldwide. Some psyllid species are important pests mainly of fruit trees, forest and ornamental plants. Despite being an economically relevant group, there are few studies on its biology, geographic distribution, natural enemies or host plant associations for many Argentinean psyllid species. This work records one species from Argentina for the first time, extends the distribution of another two psyllid species and provides information on host plants.